MANAGING RISK IN TOURISM DEVELOPMENT PROJECTS: A CASE STUDY OF NIGERIA - Oluwaseyi Alabi Awodele; Dorcas A Ayeni (Journal of Construction Project Management and Innovation)
Tourism is the fourth largest industry in the global economy. In 2009 the industry was described by the United States Institute of Peace (USIP) as an industry that helps promote peace and stability in developing countries through its jobs provision, income generation, economy diversification, environment protection and promotion of cross-cultural awareness. However, due to inherent risks in terms of some key issues, in tourism development projects, all efforts made by successive governments in Nigeria to develop this important sector of the economy have yielded few positive results. Although there had been several studies on tourism in developing countries, little is known to exist on managing risk in tourism development projects in Nigeria. The main objective of the paper therefore is to provide better understanding of risk and its management in tourism development in Nigeria. Through a sequential mixed-method approach involving a qualitative/quantitative sequence, this paper reveals that a shortage of infrastructure; poor market demand; immature financial markets; and lack of competent manpower were among the significant risk factors affecting successful development of tourism in Nigeria. The paper also identified effective mitigation measures for these risk factors. It is recommended that every stakeholder involved in tourism development projects must be involved in risk management (i.e. in identifying, analysing, developing responses, and controlling risk). Moreover, risk management should also be integrated with the decision-making processes in managing tourism development projects, as risk management reveals the rationales for making appropriate decisions.